Familial, long-term pollakisuria as initial manifestation of HSP4 due to the SPAST variant c.683-2A>C. (June 2019) - Finsterer, Josef; Wakil, Salma M.; Laccone, Franco
Highlights: Long-term pollakisuria may be the initial manifestation of HSP4. HSP4 may take a mild course over years, allowing the patients to remain in a demanding job. Typical phenotypic features of HSP4 may have a late onset. Abstract: Objective: Hereditary spastic paraplegia type-IV (HSP4) is the most common of the autosomal-dominant HSPs. Though urinary dysfunction is a frequent phenotypic feature, long-term pollakisuria as the initial manifestation of HSP4 has not been reported. Case report: The patient is a 56yo female with an uneventful history until age 46y, when she developed pollakisuria. After another 6y she developed a coordination disorder, recognized as difficulties with running and climbing stairs. Since 6 m prior to presentation, she recognized mild dysphagia. The further history was positive for strabismus, varicosity, hepatopathy, thiamin-deficiency, niacin-deficiency, lumbago, cutaneous borelliosis, abortive psoriasis, lumbar spondylosis, osteochondrosis L5/S1, and HLA-B27-positive rheumatoid arthritis. Clinical exam revealed mild weakness for left foot extension (M5-), a right subclonic patella tendon reflex, and mildly impaired left hook transition. Nerve conduction studies revealed subclinical polyneuropathy. Ophthalmologic investigations, and MRI of the brain and spinal cord were non-informative. Genetic work-up revealed the novel variant c.683-2A > C in the SPAST gene. The family history was positive for HSP in her mother and sister. Pure HSP4 was diagnosed. Conclusions: Pure HSP4 may manifest at onset with year-long pollakisuria exclusively. HSP4 may take a mild course over years, allowing the patient to do sports and to practice a demanding job.